Desempenho da cebola fertirrigada em função da adubação fosfatada - Novo Júnior, José (2014)
The municipalities of Baraúna and Mossoró-RN establishing itself as the new center for the production of onions. However, the lack of specific fertilizer recommendation for this crop in the region and to quantify parameters of fertilizer application through fertigation is an obstacle to achieving higher crop yields. Aiming to evaluate the yield and quality of onion bulbs in terms of phosphorus an experiment was conducted in the period April to September 2013, at the Experimental Farm Rafael Fernandes, Federal Rural University of Semi-Arid (UFERSA), Mossoró -RN. The experimental design was complete with six treatments and four replications blocks. The treatments consisted of doses of 0, 25, 50, 75, 100 and 125% of the recommended phosphate fertilizer for onions in the State of Pernambuco, corresponding to a fertilizer with 0.00; 33.75; 67.50; 101.25; 135.00 and 168.75 kg ha-1 P2O5, respectively. The cultivar used was Vale Ouro IPA 11. The characteristics evaluated were: plant dry matter, phosphorus content in leaf, business productivity, non-commercial productivity, total factor productivity, commercial classification of bulbs, longitudinal diameter, transverse diameter, the relationship between longitudinal and transverse diameter of the bulbs, soluble solids, titratable acidity, soluble solids ratio and acidity, poignancy, hydrogenic potential (pH) and economic indicators (gross income, net income, rate of return and profitability index). Phosphorus application did not significantly affect the quality of onion. The dose of 168.75 kg ha-1 P2O5 provided the highest business productivity, gross income, net income, rate of return and profitability index. The maximum technical efficiency for IPA 11 cultivar was obtained at a dose of 86.63 kg ha-1 of P2O5